Analysis of Islamic Communication in Improving a Positive Public Image on Ustad Felix Siauw's Instagram Account - Fariz Rizwan Siregar; Nurhanifah Nurhanifah; Bagus Prasetya; M. Al Amin; Ridho Khairul Imam (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The positive image of a person's branding is a legacy that mainly influences his career. A good image is not only to attract consumers in this case mad'u, but also for revision material and mad'u satisfaction. Each da'i has its distinctive characteristics in broadcasting Islamic teachings. Ustadz Felix Siauw uses social media, especially Instagram, to spread his da'wah by using photos, videos, colors, and infographics. This is a combination of creative forms with conservative substance. It was with this matter that Felix succeeded in attracting the attention of young people. Communicants who use Instagram no longer need to use the old method to obtain data or Islamic da'wah from selected preachers. Instagram gives the option to get data for followers. This research uses a qualitative descriptive approach, which has the aim of summarizing and describing various situations, conditions, or phenomena of social reality that exist and are interwoven in society which will become the object of research and try to draw that reality to the surface as a characteristic, character, personality, characteristic, model or reflection of the atmosphere, circumstances, or a particular phenomenon. Ustadz Felix Siauw, who is aware of the rapid development of this era, chose to use Instagram as a medium for preaching. The use of Instagram by Ustadz Felix Siauw as a da'wah media is considered successful in building a positive image in the public. The forms of communication used by Ustadz Feliz Siaw in preaching on Instagram include using captions for each article, preaching through novels, aesthetic photographs, and videos accompanied by preaching in them and using animation as an attraction in conveying the message of da'wah in it. These four forms of communication are used by Ustadz Felix Siauw in reaching out to the Islamic communication process so that the preaching messages that are informed can be accepted and understood by the public.